IMPLEMENTASI MODEL PEMBELAJARAN OUTDOOR LEARNING BERBASIS GO EXPLORE PADA LINGKUNGAN SEKITAR DI SEKOLAH ALAM MIFTAHUN NAJAH BANYUWANGI - Achmad Fatkhur Rohman; Hitta Alfi Muhimmah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning in the 21st century requires innovative approaches that are able to create meaningful, contextual, and student-centered learning experiences. One of the learning approaches increasingly implemented is Outdoor Learning, which utilizes the surrounding environment as a direct learning resource. However, the implementation of outdoor-based learning in schools remains limited and faces various challenges in its application. Therefore, this study aims to analyze the implementation of Outdoor Learning based on Go Explore at Sekolah Alam Miftahun Najah Banyuwangi, evaluate students’ learning processes, and identify character values developed through the learning activities. This study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the principal, teachers, students, and supporting school documents. The results revealed that Outdoor Learningbased on Go Explore was implemented systematically, planned comprehensively, and continuously. The learning process contributed positively to the development of character values and enhanced students’ motivation and meaningful learning experiences through direct interaction with the environment.